Quantitative Analysis of Spoken Discourse Using Memoirs of Old-time Moviegoers. Issue 3 (3rd July 2022) - Çalışkan, S.; Can, F.; Akbulut, H.; Öztürk, S. R.
ABSTRACT: We present the first quantitative analysis of spoken discourse for the Turkish language using memoirs of a group of old-time moviegoers of varying age groups whose birth year spreads over a period of four decades ranging from the 1930s to the 1960s. They tell their experiences by answering a set of questions. Their responses are evaluated comprehensively with the expectation that various attributes of the participants are reflected by their everyday speaking language. We also investigate their language characteristics in terms of their vocabulary richness and word usage. The results show that the age and gender of the participants can be inferred to some extent from their speech, as is the case for written text. However, the difference is not significant in the language use of younger and older respondents in terms of vocabulary richness and archaic word usage. With additional data obtained for some participants, it is shown that text can be accurately identified as being either spoken or written; however, the spoken text of a person can only be differentiated from their written text with the accuracy level of a random guess.